Adult stuttering and attentional ability: A meta-analytic review. (3rd July 2020) - Doneva, Silviya P.
Abstract: Purpose : The study presents the first review in which the link between attentional ability and developmental stuttering is explored. The review aimed to summarise the published research literature and provide a more conclusive understanding as to the relationship between stuttering and attention. Method : To be included in this review, the studies had to compare the attentional performance of adult people who stutter (PWS) and people who do not stutter (PWNS) over the age of 18 years with a validated psychometric instrument for measuring attentional ability. Articles were searched in four electronic databases where each of the following search terms (attention, vigilance, inhibitory, inhibition, interference, executive and processing) was cross-referenced with each of the following terms (stutter, stammer, speech disfluency and speech dysfluency). A total of 21 studies met the inclusion criteria to be submitted into a meta-analysis. Result : The results of the main meta-analysis, which included all selected studies, demonstrated that PWS had a significantly worse attentional performance as compared to PWNS. Two further meta-analyses on selective attention and dual tasking performance confirmed the latter finding. Importantly, however, the effect was not present in all studies. Conclusion : Our findings should be taken as an indication that stuttering sometimes (but not always) manifests together with poorer attentional ability, such that the identified link does not affect all PWS. These results provide support for the notion that there is a close association between stuttering and attentional ability in a subgroup of PWS, highlighting potential practical implications for stuttering treatment.